(untitled) (Research, Society and Development, 2020)
With the emergence of the new coronavirus in China and its rapid spread around the world, the World Health Organization classified the COVID-19 outbreak as a pandemic bringing radical changes to many countries. Several dimensions of society were affected, including education. While some institutions decided to paralyze their activities, others decided to adopt emergency remote teaching as a way to maintain education. In this sense, knowing the relationship between cyberculture and knowledge is fundamental to propose educational practices mediated by Information and Communication Digital Technologies in the pandemic context. This article aims to explore the pedagogical practices adopted by the Postgraduate Program in Vocational and Technological Education in order to maintain academic activities during the COVID-19 pandemic. To this end, the bibliographic and exploratory researches were adopted to map the activities carried out throughout the discipline Educational Practices in Vocational and Technological Education and to deepen the knowledge on emergency remote teaching and its impacts on the teaching and learning process. The study concluded that emergency remote teaching contributed to the achievement of the discipline Educational Practices in Vocational and Technological Education in an integrated manner with the assumptions of polytechnic and omnilateral education.